Pengaruh Kualitas Sistem, Kualitas Informasi, Dan Kualitas Pelayanan Sistem Informasi Akademik (Sisfo) Unisma Terhadap Kepuasan Mahasiswa (Pada Mahasiswa FEB Universitas Islam Malang Angkatan 2016) - Saniasah Saniasah; M. Hufron; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis study aims to determine the effect of system quality, information quality, and service quality of UNISMA's academic information system (SISFO) on student satisfaction either simultaneously or partially. The population in this study amounted to 875 students (at FEB Malang Islamic University Students, Class of 2016) and the sample in this study was calculated using the Slovin formula with a total of 90 respondents. Collecting data through distributing questionnaires online using google form. Data analysis using multiple linear regression. The results of the analysis show that the quality of the system, the quality of information and the quality of service simultaneously have a significant positive effect on student satisfaction while the partial quality of the system and the quality of information are not significant on student satisfaction, while the quality of service has a significant positive effect on student satisfaction.Keywords: system quality, information quality, service quality, student satisfaction.